Login di Close The Door : Dakwah Digital Habib Ja'far Pada Generasi Z - Husna, Nihayatul (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2023)
The rapid progress of information and communication technology, especially in mass media or social networks, requires people to be aware of the importance of learning to use media. Generation Z is no exception, who from an early age are familiar with technology and are familiar with gadgets. Individuals within the scope of generation Z tend to utilize the mass media as a means of transferring information or even knowledge. Of course there are positive effects in the use of this mass media. One of them is as a means of broadcasting Islamic da'wah on social media. Broadcasting Islamic da'wah through various social media platforms, such as Instagram, YouTube, Tik-Tok, Podcasts, Twitter and Facebook. Not long ago, during the month of Ramadan in 1444 H Deddy Corbuzier held a special event "Login" on his official YouTube channel. Interestingly, the "Log In" event is part of Islamic da'wah which is presented in the form of a dialogue between Habib Ja'far and Onad who is a non-Muslim. This relaxed delivery of Islamic da'wah invites enthusiasm for generation Z to further explore Islamic teachings, which so far have tended to be conveyed formally and seem rigid. So it is important to examine further about the essence of Islamic da'wah presented in this "Login" program. This research is related to the delivery of Islamic da'wah in the "Login" event using a qualitative descriptive research method. The resulting data comes from videos on YouTube which are then compiled using valid theoretical sentences.